Hasil Belajar dan Kreativitas Siswa Dalam Model Pembelajaran Project-Based Learning Pembuatan Video Pembelajaran Tema Pemodelan UML - Umiyati, Tri (Didaktika, 2022)
Technological developments, especially in the field of education, are generally aimed at advancing student motivation to be superior and more advanced in the use of technology so that education will be more advanced. From the statement above, many educators try several technologies to facilitate learning. Likewise in this study which has the aim to determine the effect of applying the PjBL (project-based learning) learning model on learning outcomes in Software and Games Development (PPLG) vocational major in State Vocational School of 1 Wadaslintang. This study used a qualitative approach with observational method. The form of qualitative is taken by observing the activities during practicum class with creativity project. The research sample consisted of 34 students with 14 groups, each group consisting of 2 to 3 students from class XI PPLG 1 as an observational class. Data analysis in this study used an animated video project. Based on the results of data analysis, there were results of student projects with high creativity different in those groups. This result indicated that in learning video making, project-based learning successfully inhibits the learning outcomes and students' creativity. It should be from the mix matching the project-based approach with the alternative activities. This is can be a basis for educators to implement similar approaches for other project-based activities